2012
DOI: 10.1056/nejmc1207269
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin and the Risk of Cardiovascular Death

Abstract: BACKGROUND-Although several macrolide antibiotics are proarrhythmic and associated with an increased risk of sudden cardiac death, azithromycin is thought to have minimal cardiotoxicity. However, published reports of arrhythmias suggest that azithromycin may increase the risk of cardiovascular death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…For instance, cefotaxime (a third-generation cephalosporin) was more commonly used in newborns under 3 months of age, but azithromycin was rarely administered in that age group. This observation might reflect the results of some published studies which reported an increased risk of cardiovascular death associated with the use of azithromycin, specifically, in infants [25,26].…”
Section: Resultssupporting
confidence: 70%
“…For instance, cefotaxime (a third-generation cephalosporin) was more commonly used in newborns under 3 months of age, but azithromycin was rarely administered in that age group. This observation might reflect the results of some published studies which reported an increased risk of cardiovascular death associated with the use of azithromycin, specifically, in infants [25,26].…”
Section: Resultssupporting
confidence: 70%
“…10, 11 While Ray et al used appropriate analytic methodologies to attempt to correct for any confounding bias intrinsic to the observational, nonrandomized nature of the study design, due to a higher prevalence of comorbid/co-existing conditions and increased mortality rates associated with Medicaid beneficiaries in the United States, legitimate questions were raised about whether the results of the study could be generalized to populations with substantially lower baseline CV disease risk and if differences in the baseline characteristics of the treatment groups were adequately controlled. 12, 13 …”
mentioning
confidence: 99%
“…In the COVID-19 era, azithromycin is used daily for its anti-inflammatory and bacterial preventive properties, but the exact benefit is not fully understood [ 92 , 93 ]. The use of azithromycin in COVID-19 patients is not well established and is still debated, while adverse effects such as prolongation of the QT interval could potentially increase the risk of sudden cardiac death in non-monitored patients [ 94 ] ( Table 2 , Figure 2 ).…”
Section: Anti-inflammatory Agents and Treatment Optionsmentioning
confidence: 99%